(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The quality movement has gone through many transformations. Earlier Quality and now Excellence is gaining attention in today’s global competitive scenario. The quality award models, such as the Malcolm Baldrige National Quality Award (MBNQA) and the European Foundation for Quality Management (EFQM) Excellence Model, Deming Model are used as a guide and standard to achieve Quality and Excellence in Business. The purpose of this paper is to make comprehensive study and analysis of these Business Excellence Models. This research is an attempt to find out distinction between Quality and Excellence. It also covers similarities, variation and casual linkage between core value and procedures of selected models.Quality and Excellence are an important competitive factor or achieving competitive advantage and is also considered as an essential seal of approval in the eyes of customers. Earlier Quality and now Excellence is and was always being a major concern since World War II. The wave of globalisation makes "The customer king," truer than ever before. The society has become knowledgeable and selective while making purchase decisions which results in the shift towards customer focused strategies. The criteria for success in this global, internationally oriented market have been changing rapidly. Excellence is imperative in order to expand business, enter new markets, and set realistic, competitive long-term objectives. The Quality and Excellence of the product or service offered is pre-requisite, an entry requirement for any company that wants to remain successful over the years. The Quality Literature and various studies witnessed Quality and Excellence has becoming significant factor in the business strategy planning process in order to respond the highly competitive environment and the market’s expectations. These days, Business Excellence (BE) is one of the most popular approaches which is being used when we discussed Quality. Therefore it is important for the organisation regardless of industry, size, structure or stage of development to formulate effective approaches to enhance their management efficiencies and capabilities to achieve Total Quality and Business Excellence (BE).